On a class of homeomorphisms of function spaces preserving the Lindelöf number of domains - Lazarev, Vadim R. (Вестник Томского государственного университета. Математика и механика)
We consider the class of all homeomorphisms between the function spaces of the form Cp(X), Cp(Y) such that the images of Y and X under their dual and, respectively, inverse dual mappings consist of finitely supported functionals. We prove that if a homeomorphism belongs to this class, then Lindelöf numbers l(X) and l(Y) are equal. This result generalizes the known theorem of A. Bouziad for linear homeomorphisms of function spaces